LEGAL PROTECTION OF CREDITORS AGAINST THE EXECUTION OF COLLATERAL OBJECTS IN THE EVENT OF THE DEBTOR'S BREACH OF PROMISE AT BANK MANDIRI KC SURABAYA GENTENGKALI - Reza Nugraha Putra; Waluyo (Universitas Islam Balitar, 2023)
When the debtor neglects to make payments on his debt, an execution parate is made as a form of legal protection for creditors. The origin of the execution of mortgage rights can be traced back to this time. UUHT has provided a precise description of the execution that can be carried out in the event of a debtor's default, including holding an auction known as